RESULTS OF EXPERIMENTAL INFECTION OF TURKEYS WITH A/DUCK/ALTAI/469/14 H5N1 STRAIN OF AVIAN INFLUENZA VIRUS - V. Yu. Sosipatorova; D. A. Altunin; I. A. Chvala; N. S. Mudrak; D. B. Andreychuk (Ветеринария сегодня)
The data on experimental infection of 6-week-old Big-6 cross turkeys with an epidemic A/duck/Altai/469/14 H5N1 clade 2.3.2.1c strain of avian influenza virus are presented. The characteristics of the infection process in birds inoculated intranasally at a dose of 5.0 lg EID50/0.5 cm3 are described with an indication of the incubation period and the mean time of death. The pathomorphological changes at the tissue and cellular level are shown based on histological and immunohistochemical studies of fragments of respiratory, digestive, cardiovascular, nervous, excretory, lymphoid and muscular systems of experimental birds. The testing was carried out using paired preparations of paraffin-embedded tissue sections from experimentally infected and healthy turkeys. One sample was subjected to histological staining using hematoxylin and eosin dyes, and its duplicate was subjected to immunohistochemical assay using a preparation of polyclonal antibodies as primary antibodies against the ribonucleoprotein of avian influenza virus. The results of histological and immunohistochemical studies are photodocumented and presented in the paper. Inflammatory and necrotic lesions of varying severity are detected in the preparations of the trachea, lung, muscular stomach, glandular stomach, small intestine, large intestine, pancreas, brain, cerebellum, heart, kidneys, liver and spleen of turkeys. Immunohistochemical analysis showed the greatest distribution of the influenza virus antigen in the cerebral endothelium, cerebellar Purkinje neurons, acinar cells of the pancreas and in myocardiocytes of the heart. In the course of the experiment it was established that A/duck/Altai/469/14 H5N1 caused a generalized form of infection in turkeys with clinical and pathologic lesions characteristic of highly pathogenic avian influenza.